Detrimental Effects of Workplace Bullying: Impediment of Self-Management Competence via Psychological Distress - Giorgi, Gabriele; Perminienė, Milda; Montani, Francesco; Fiz-Perez, Javier; Mucci, Nicola; Arcangeli, Giulio (Frontiers in Psychology, 2016)
Emotional intelligence has been linked to various positive outcomes, such as organizational effectiveness, commitment, morale and health. In addition, longitudinal studies demonstrate that the competencies of emotional intelligence may change and be developed over time. Researchers have argued that work relationships are important for the development of emotional competence, but their usefulness depends on the quality of the relationship. Workplace bullying is considered to be one of the most stressful phenomena in the workplace and an example of a dysfunctional and toxic relationship that has detrimental effects on an individual’s physical and psychological health. Hence, the objective of the present study was to analyze the relationship linking workplace bullying, psychological distress and the self-management competence of emotional intelligence. More specifically, we tested part of the model presented by Cherniss and Goleman (2001) in which researchers argued that individual emotional intelligence is a result of relationships at work. In addition, we extended the model by proposing that the relationship between exposure to workplace bullying and the competence of self-management is explained by psychological distress. Data analysis of 326 participants from two private sector organizations in Italy demonstrated that psychological distress fully mediated the relationship between workplace bullying and the emotional intelligence ability of self-management. The present study’s findings point to the idea that, not only may emotional intelligence assist in handling exposure to workplace bullying, but exposure to workplace bullying may impede emotional intelligence via psychological distress.